(untitled) (Journal of Academic Research, 2020)
In recent years, caffeine received increasing attention in food and pharmaceutical industries, due to its pharmacological properties which comprise stimulation of the central nervous system, peripheral vasoconstriction, relaxation of the smooth muscle and myocardial stimulation. The aim of this study was to determine the content of caffeine in eight types of tea (green, black) and four types of coffee. The content of caffeine was determined by using Spectrophotometric method. The content of caffeine has been associated with plant origin and growth conditions, as well as processing conditions. The results of the present study showed that the pH values ​​of tea and coffee samples ranged between (6.10-4.81) and the moisture values ​​in the tea samples ranged between 2.04-8.10% where the lowest value was for T4 sample and the highest value for sample T8. While, the ash content of tea samples ranged between 4.71-7.52% and C12 sample was recorded the highest ash content in coffee samples with value 4.86%. The amount of caffeine was quantified by employing UV-vis Spectrophotometric technique at different conditions, the concentration of the caffeine in the tea and coffee solution was determined at different brewing time (1, 3 and 5 min), water volume (30, 70 and 150 ml) and temperature (80, 90 and 100 °C), where the maximum effect was at 100 ° C and 5 min, while the volume of the solution did not significantly affect the concentration of caffeine in the sample extract.